The right to evidence electronic governance and access to official records in Malaysia - International Record Management Trust; Arkib Negara Malaysia (Kuala Lumpur : Arkib Negara Malaysia, 1999)
The documentary video explores the relationship between the Malaysian Government's vision of harnessing information technology to improve and empower the lives of citizens and the parallel requirement to access and manage evidence in the electronic age.
Keywords: Public administration -- Data processing